Molecular structure characterization of the tetrahydrofuran-microwave-extracted portions from three Chinese low-rank coals. (1st February 2017) - Zhang, Liangping; Hu, Song; Chen, Qindong; Xiao, Lingfeng; Syed-Hassan, Syed Shatir A.; Jiang, Long; Wang, Yi; Su, Sheng; Xiang, Jun
Graphical abstract: Highlights: The TME portions were rich in highly branched aliphatic hydrocarbons. Aromatic structures in the TME portions were mainly para -alkyl substituted. CO bonds were the main oxygen-containing structures in the TME portions. AMW of specific fraction had positive relationship with parameter I2 . Abstract: The existence form and structure properties of mobile phase (MP) in low-rank coals (LRCs) can significantly influence the initial stage of thermal conversion. In the present work, three Chinese LRCs, namely, Shenfu, Zhundong and Hongshaquan, were extracted with tetrahydrofuran using the microwave-assisted heating. The tetrahydrofuran-microwave-extracted (TME) portion as the representative of MP was further separated to four fractions defined as oil, resin, asphaltene and preasphaltene, respectively. Diffuse reflectance Fourier transform-infrared spectroscopy (DRIFT), gas chromatography/mass spectrometer (GC/MS), matrix-assisted laser desorption ionization time-of-flight mass spectrometer (MALDI-TOF-MS) and X-ray photoelectron spectroscopy (XPS) were used to comprehensively investigate the molecular characteristics of the derived materials. The results indicated that the studied TME portions were mainly consisted of asphaltenes and rich in highly branched aliphatic hydrocarbons due to the relatively low CH2 /CH3 and Har /Hal ratios. Para -alkyl substituted aromatic structures with 1–2 rings were the main aromatic structures in the TME portions. CO bonds were the main oxygen-containing structures in the TME portions and could be more likely seen in aliphatic compounds. Combining the MALDI-TOF-MS and DRIFT analyses, the ratio of aliphatic side chains and aromatic hydrogens (3000–2800 cm −1 /900–700 cm −1, I2 ) derived from IR spectra seemed to be a suitable parameter for assessing the average molecular weight (AMW) of the specific fraction in TME portion of LRCs when the ratio of CO/CO was at very low level. The results made a further explanation for the detailed chemical structure of mobile phase in coal and could be helpful for studying the formation mechanism of volatiles during pyrolysis process.